INFLATION AND INFLATION EXPECTATIONS IN CONDITIONS OF SATELLITE INDEPENDENCE - Петрик, Олександр; Дейсан, Ігор (Socio-economic relations in the digital society, 2019)
The article reflects the main provisions of the modern new classical theory and the possibility of their practical application in the activities of central banks. It is established that the monetary policy is aimed at ensuring low inflation in the long run. In the short run, monetary policy stabilizes fl uctuations in the GDP gap from the long-term trend (potential GDP growth). Despite the fact that the overwhelming number of modern central banks have a priority goal of ensuring price stability, they are also trying to stabilize the growth of the real sector of the economy within their own capabilities. Such a deviation is usually measured by breaking the current and potential release. Thus, the actions of monetary policy can be conditionally defi ned as minimizing losses due to deviations of infl ation from the target indicator and deviations of the current output from its potential level using the quadratic loss function. It has been determined that central banks applying active monetary policy publicly proclaim changes (or immutability) of monetary policy in order to achieve the main goal in the long term and stabilize the impact on economic activity in the short term. Th e main change in monetary policy is the decision to change the key short-term rate of the central bank. It has been proven that the monetary policy has become more transparent due to qualitative changes in the communications of the central bank with the company in order to bring infl ationary expectations to the level of a long-term infl ation target and to keep them at this level. It was concluded that an anti-infl ationary policy based on well-defined rules and an increase in confi dence can reduce infl ation and keep it low without signifi cantly reducing output. The following practical experience of dozens and dozens of countries confi rmed the correctness of this approach and that is why it is now dominant in the world.
Keywords: inflation; inflation expectations; monetary policy; uncertainty; central bank